Relação entre o ciclo sono e vigília e a função cardiorrespiratória em estudantes de medicina - Xavier, Rafaella Kaline Costa (2010)
Students, normally, present an irregular sleep pattern characterized by delays in sleep onset and offset from weekdays to weekends, short sleep duration on weekdays and long sleep duration on weekends. The reduction of the necessary sleep and the irregularity in the sleep patterns provoke relevant short- and long-term impairments on performances, for example, in cardiorespiratory function. The cardiorespiratory performance represents, in addition to fitness, traces associated to health conditions and in several studies to pattern and/or individual s sleep quality. The aim of this study was to evaluate the pattern of the sleep-wake cycle and the cardiorespiratory function of medical students under different class schedules. The study was accomplished with two classes of medical students of UFRN, one had classes at 7 am (n = 47) and the second had classes at 8 am (n = 41) during the week. On the first stage of the study all volunteers filled out an anamnesis, the International Physical Activity questionnaire, the Pittsburgh index of sleep quality, the Portuguese version of the Horne and Östberg cronotype questionnaire, the Health and Sleep questionnaire and the Epworth Scale of Somnolence (ESS). On the second stage, 24 students (12 of each class) had their activity rhythm monitored by actimeters set to record activity at a 2-min interval for 14 days concomitant to the completion of the sleep diary. In this same stage, each volunteer performed the effort test (treadmill) only once in the morning period (between 9:00 and 11:00). The students showed an irregular pattern of the sleep-wake cycle and this irregularity is strongly influenced by the class schedules, in addition to the contribution of the academic demand, social activities and endogenous factors. The students who woke up earlier showed greater irregularity in the sleep-wake pattern. The earlier was the class schedule the worse was the sleep quality and the greater was the frequency of students with excessive diurnal somnolence. The classes schedules and the irregular pattern of the sleep-wake cycle did not show effect on the cardiorespiratory performance of the medical students. The performance on the test seems to be affected by other factors, which can be related to the pattern of the sleep-wake cycle or not. Therefore, it is suggested that the late start of classes provokes less irregularity on the pattern of the sleep-wake cycle. However, it was observed that this irregularity and the class schedule seem not to affect the cardiorespiratory performance directly